2012
DOI: 10.1099/vir.0.036087-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the STAT6 transcription factor in Jurkat T-cells by the herpesvirus saimiri Tip protein

Abstract: Herpesvirus saimiri (HVS), a T-lymphotropic monkey herpesvirus, induces fulminant T-cell lymphoma in non-natural primate hosts. In addition, it can immortalize human T-cells in vitro. HVS tyrosine kinase-interacting protein (Tip) is an essential viral gene required for T-cell transformation both in vitro and in vivo. In this study, we found that Tip interacts with the STAT6 transcription factor and induces phosphorylation of STAT6 in T-cells. The interaction with STAT6 requires the Tyr127 residue and Lck-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…We could not exclude the possibility that cleaved STAT6 induced by LANA is not generated in the nucleus but is present in the cytoplasmic fraction due to protein shuttling. For example, recent reports have shown that STAT6 phosphorylation on Tyr 641 was induced by viral or parasitic infection independent of IL-4 [2527]. However, the canonical STAT6 signaling induced by IL-4 is independent of STING or MAVS, which help viruses trigger STAT6 phosphorylation [28].…”
Section: Discussionmentioning
confidence: 99%
“…We could not exclude the possibility that cleaved STAT6 induced by LANA is not generated in the nucleus but is present in the cytoplasmic fraction due to protein shuttling. For example, recent reports have shown that STAT6 phosphorylation on Tyr 641 was induced by viral or parasitic infection independent of IL-4 [2527]. However, the canonical STAT6 signaling induced by IL-4 is independent of STING or MAVS, which help viruses trigger STAT6 phosphorylation [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ANXA2 can contribute to prostate cancer metastasis by interacting with the transcription factor STAT6 [25]. STAT6 can translocate to the cell nucleus where it acts as a transcription activator [26]. Interestingly, we found that in tissues with lymph node metastases, ANXA2 was mainly located in the nucleus (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…For instances, herpesvirus saimiri (HVS)-encoded Tip (tyrosine kinase-interacting protein) could interact with STAT6 and induce phosphorylation in T cells (22); SHP1 expression was selectively downregulated in human T-cell leukemia virus 1 (HTLV-1)-transformed T-cell lines, and Tax transactivates IL-13 overexpression (43,44). In addition, EBV Zta protein is able to induce the expression of IL-13 and promote the proliferation of EBV-infected B cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, STAT6 is constitutively activated in primary mediastinal large B-cell lymphomas due to amplification of JAK2 (13), while in hepatocellular carcinoma, gastric carcinoma, colorectal cancer, and hematological malignancies, STAT6 activation results from promoter hypermethylation and silencing of SHP1 or SOCS1 (17)(18)(19)(20). Interestingly, in virus-associated diseases, constitutive STAT6 activation occurs through different pathways (21)(22)(23). We and other colleagues recently found that in KSHV-associated cancers, IL-4-mediated STAT6 activation is tightly regulated by the virus in order to switch life cycles from latency to lytic replication (24,25).…”
mentioning
confidence: 99%